PERSEPSI MAHASISWA FIP TERHADAP KUALITAS PENGAJARAN DOSEN PRAKTISI MENGAJAR DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Mallombasi, A. Malik; Sumarlin Mus; Ahmad Restani Syukron Thayyib (Yayasan Nusantara Hasana Berdikari, 2025)
Improving the quality of teaching in higher education is a strategic agenda in supporting the readiness of graduates to face the demands of a dynamic world of work. The “Teaching Practitioner” program initiated by the Ministry of Education, Culture, Research, and Technology aims to enrich the learning process through the involvement of professional practitioners as lecturers in higher education. This study aims to evaluate the perceptions of students of the Faculty of Education, Makassar State University towards the quality of teaching by practitioner lecturers involved in the program. Using a quantitative approach with a descriptive design, data were collected through a closed questionnaire based on a semantic scale distributed to 376 students, with descriptive statistical analysis to describe perceptions in five main dimensions: mastery of material, attitude and professionalism, communication skills, teaching skills, and ability to motivate students. The results showed that students gave very good to good ratings on all dimensions evaluated, reflecting the success of practitioner lecturers' teaching in meeting academic expectations and students' learning needs. These findings emphasize the relevance of integrating professional practitioners into the academic environment and the importance of strengthening the pedagogical and communication competencies of non-academic teachers. The contribution of this research is not only to provide empirical data that supports the effectiveness of the “Teaching Practitioner” program but also to offer theoretical and practical insights for policy makers, program managers, and educators in designing teaching strategies that are more responsive to the development of higher education and the needs of the world of work.